1981
DOI: 10.1002/ana.410100604
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental neutron activation analysis of brain aluminum in Alzheimer disease and aging

Abstract: Instrumental neutron activation analysis procedures were used to determine the aluminum content of various brain regions in histologically verified Alzheimer disease (AD) and in controls. The grand mean aluminum level for 74 AD specimens was 0.372 +/- 0.058 microgram/gm and for 137 adult controls, 0.467 +/- 0.033 microgram/gm, both on a wet weight basis. No difference was found at the bulk sample level between AD and adult controls, corrected for age and sex, or when frontal, temporal, and hippocampal specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(59 citation statements)
references
References 21 publications
4
55
0
Order By: Relevance
“…3,4) In fact, some evidence supports the selective accumulation of Al within neurons containing neurofibrillay tangles in patients with Alzheimer's disease and within the aging human brain. 1,5) Meiri et al, have also reported that brain Al concentrations reach submilimolar levels in some encephalopathies.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…3,4) In fact, some evidence supports the selective accumulation of Al within neurons containing neurofibrillay tangles in patients with Alzheimer's disease and within the aging human brain. 1,5) Meiri et al, have also reported that brain Al concentrations reach submilimolar levels in some encephalopathies.…”
mentioning
confidence: 96%
“…3,4) In fact, some evidence supports the selective accumulation of Al within neurons containing neurofibrillay tangles in patients with Alzheimer's disease and within the aging human brain. 1,5) Meiri et al, have also reported that brain Al concentrations reach submilimolar levels in some encephalopathies.6) Several lines of research that use cultured cells and the aluminum-maltolate complex (Al(maltol) 3 ), which is a membrane permeable, lipophilic complex of Al, also showed that the exposure of cells such as the Neuro-2a murine neuroblastoma cells, 7) human NT2 neuroblastoma cells, 8) and PC12 cells 9,10) to the Al complex results in a decrease in cell viability via the apoptotic cell death pathway. Recently, we have reported that the treatment of PC12 cells with Al(maltol) 3 causes a decrease in the levels of the intracellular reduced glutathione depending on the amount of Al(maltol) 3 accumulated in the cells.…”
mentioning
confidence: 99%
“…Even though the role of Al in many neurodegenerative diseases is still uncertain (McDermitt et al, 1979;Markesbery et al, 1981), the mechanisms of Al accumulation in AD and experimental mammalian brains and the cholinergic dysfunction have continued to receive much attention. Attempts have been made to develop an animal model of AD that could mimic the neuropathological changes and cholinergic deficit in the AD brain using Al as a cholinergic neurotoxin (Kosik et al, 1983;Wisniewski et al, 1990).…”
mentioning
confidence: 99%
“…Increased amounts of aluminum have been reported in brains of individuals dying with Alzheimer's disease compared to nondemented controls (68). Attempts to reproduce this finding have produced varying results and remain controversial (69).…”
Section: Aluminum Adverse Health Effects Of Aluminum Exposuresmentioning
confidence: 99%